High growth firms and job creation in Finland - Matthias Deschryvere (The Research Institute of the Finnish Economy (ETLA), 2008)
The goal of this descriptive paper is to identify which firms add the most employment in Finland. The analysis is based on firm and establishment data from the Finnish Business Register (period 2003-2006). It is found that in 2006 Finland had 750 High Growth Firms (according to the OECD-definition). This represents roughly 5% of the firms with at least 10 employees. As growth has a multi-facetted nature it is crucial to not only focus on how much a firm grows but also how it grows. Not all of those 750 HGF's grew organically. In fact, of all the jobs they created 65% turned out to be organic employment. There seems to be a positive relationship between the initial size of a HGF and what proportion of the employment is acquired. Correcting for acquisition growth leaves us with 642 organic HGF's. The share of HGF's was the highest in the sectors 'other business activities', 'computer and related activities' and 'health and social work'. It does look like a substantial number of HGF's have been expanding due to trends in domestic outsourcing. Future research should focus on the causes and consequences of the expansion of those firms. Firm group information should be used as to be able to better capture shifts of employment between firms of the same group.
Keywords: D21; L25; M13; O12; O40; 330; Firm growth; High growth firms; Job creation; growth patterns; Unternehmensentwicklung; Beschäftigung; Beschäftigungseffekt; Finnland